An enumeration of orphans and analysis of the problems and wishes of orphans: the case of Kariba, Zimbabwe - Jaqualine F Mangoma (SAHARA-J, 2008)
In southern Africa, HIV and AIDS accounts for the largest proportion of orphans. Very often the orphaned children become destitute, and young girls in particular become more vulnerable to HIV and AIDS as they try to fend for the rest of the family. This paper reports on the number of orphans in Kariba, Zimbabwe, describing their problems, coping strategies and wishes. The study was carried out in Nyamhunga and Mahombekombe high-density residential areas of Kariba, Zimbabwe. All households in the study area were visited, and a semi-structured questionnaire aimed at enumerating orphans and obtaining information regarding general problems of orphans was administered to heads of households present. In addition, information on the plight, coping strategies and survival wishes of orphans were collected through 15 focus group discussions held with orphans, care givers, community leaders and stakeholders. The prevalence of orphans in Kariba, based on a sample of 3 976 households, was found to be very high (56%) with most of the orphans in the age group 6 – 12 years. The majority of the orphans were paternal and under maternal care. Over 30% of the orphans of schoolgoing age were not in school, and some young girl orphans became involved in commercial sex work. The survival wish list of the orphans included school fees, accommodation, health care provision, adequate food and income-generating projects. However, suggestions on orphan care and needs given by community members were somewhat divergent from the orphans' wish list, indicating that community interventions may not be sensitive to the wishes of those affected. Although the study did not categorise orphans according to cause of death of parents, there are indications that most of the orphans are accounted for by HIV and AIDS.